Evaluation of Precision Feeding SID Lysine to Lactating Sows on Sow and Litter Performance, Nitrogen Level, and Feed Cost - Mikayla S. Spinler; Jordan T. Gebhardt; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Hyatt L. Frobose; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 95 mixed parity sows (DNA 241) and litters (DNA 241 × 600) were used across four batch farrowing groups to evaluate the effects of precision feeding Lys during lactation. Sows were blocked by parity and allotted to 1 of 3 treatments on day 2 (the day after farrowing) of lactation. Dietary treatments were formed by using 2 diets: a low Lys diet (0.25% SID Lys) and a high Lys diet (1.10% SID Lys). Treatments included a control, NRC (2012), or INRA (2009) treatment curve. Sows on the NRC or INRA treatment curves received a blend of the low and high diet using the Gestal Quattro Opti Feeder (Jyga Technologies, St-Lambert-de-Lauzon, Quebec, Canada) to target a specific SID g/d of Lys intake for each day of lactation based on the NRC and INRA models for each sow parity and litter size combination. Sows on the control treatment received only the high Lys diet with no diet blending or specific g/d of Lys target. Sows were allowedad libitumaccess to feed throughout lactation. Lysine intake was 102% of targeted average g/d of Lys intake during lactation for sows fed the NRC treatment curve and 98% of targeted average g/d for sows fed the INRA treatment curves. Sows fed only the high Lys diet (control) had greater (P<0.05) average g/d of Lys intake compared to sows fed either the NRC or INRA treatment curves. No differences (P>0.05) in sow weight, backfat, caliper score, or loin depth change were observed among treatments. However, litters from sows fed the control treatment had greater (P<0.05) litter weight on d 9 and weaning compared to litters from sows fed either the NRC or INRA treatment curves. Pigs from sows fed the control treatment had greater (P<0.05) BW at weaning and preweaning ADG compared to pigs from sows fed the INRA treatment curve, with pigs from sows fed the NRC treatment curve intermediate. Sows fed the NRC treatment curve had a greater (P<0.05) feed cost per lb of litter gain compared to sows fed the control treatment, with sows fed the INRA treatment curve intermediate. This was unexpected because sows fed the NRC treatment curves had a blend of the low and high Lys diets which had a decreased feed cost per lb compared to the control diet. However, this was the result of higher feed intake of sows fed the NRC treatment curve. Sows fed the control treatment had the highest (P<0.05) N excretion and sows fed the INRA treatment curve the lowest, with sows fed the NRC treatment curve intermediate. Sows fed the control treatment had greater (P<0.05) serum urea nitrogen concentration on d 9 and at weaning compared to sows fed the NRC and INRA treatment curves. In summary, pigs from sows fed a single diet (control) that did not utilize feed blending had increased pig growth performance during lactation compared to pigs from sows fed the NRC or INRA treatment curves. This is likely because the NRC and INRA estimated Lys requirements are too low to maximize litter growth performance and not because they were on a feed blending curve. Future research should be aimed at examining the effects of blending high and low Lys diets, while providing daily Lys intakes with greater dietary SID Lys concentrations, to achieve similar litter growth performance compared to conventional feeding of a high Lys diet.
Keywords: lysine level; precision feeding; sows